Insecticida Test Of Attractive Oil On Clove (Syzygium Aromaticum (L.) Merr. & Perry.) Leaves Against Aedes Aegypti Mosquito - Agustin, Rekha Yulia; Marcellia, Selvi; Susanti, Dwi (Jurnal Ilmu Kedokteran dan Kesehatan, 2024)
Clove leaves (Syzygium aromaticum (L.) Merr. & Perry.)  have eugenol compounds in essential oils which have the potential as natural insecticides. The purpose of this study was to determine the effectiveness of essential oil insecticides on clove leaves (Syzygium aromaticum (L.) Merr. & Perry.)  in killing Aedes aegypti mosquitoes. This study used the distillation method with air as a solvent. The concentrations of clove leaf essential oil extract used were 0.5%s, 1%, 2.5% and 4%. The results of the LC50 test showed that clove leaf essential oil (Syzygium aromaticum) was effective in killing Aedes aegypti mosquitoes with an LC50 value of 0.993% and was included in the very toxic category. The higher the concentration of essential oils, the greater the killing activity and the lower the LC50 value, the higher the effectiveness in killing Aedes aegypti mosquitoes. It can be concluded from this study that clove leaf essential oil (Syzygium aromaticum (L.) Merr. & Perry.) has effectiveness as a natural insecticide against Aedes aegypti mosquitoes, can be seen from the mortality value in the 55th minute of 100% at a concentration of 4%.